Systematic Review: Impact of Bisphenol-A (BPA) Exposure on Human Health - Sulistiyani, Sulistiyani; Okti Iswari Triswindyaningrum; Yusniar Hanani Darundiati (Universitas Airlangga, 2025)
Introduction: One chemical substance used in producing epoxy resins and polycarbonate (PC) is called bisphenol-A (BPA). Three million tons of the chemical compound bisphenol-A are still produced annually. The amount of BPA produced in 2015 was 7.7 million tons; by 2022, 10.8 million tons are anticipated to be made. This study aimed to ascertain the effects of bisphenol-A exposure on human health. Discussion: This study used a systematic review method by collecting articles through online databases with a publication range of 2018 - 2024. The article search used the PRISMA flow diagram. The findings of 30 articles all examined the impact of BPA exposure on health. The level of exposure to bisphenol-A can have an impact on health due to the nature of BPA EDC (Endocrine Disrupting Hormone) which can inhibit the activity of natural hormones in the body. Conclusion: The impact on human health due to exposure to bisphenol-A such as cancer, obesity, disruption of reproductive health, hypertension, disrupting child development, and also behavioral changes in children. Bisphenol-A enters the body not only through food packaging but also through air and dust contaminated with BPA. The length of exposure and concentration of BPA affect its effects on the human body.